IMPLEMENTATION OF THE REGIONAL GOVERNMENT INFORMATION SYSTEM (SIPD) IN FINANCIAL REPORTING AT THE REGIONAL REVENUE AGENCY OF NORTH SUMATRA PROVINCE - Rossilawati, Nita; Junita, Audia; Adam (Pena Cendekia Insani, 2026)
This study aims to analyze the implementation of the Regional Government Information System (SIPD) in financial reporting at the Regional Revenue Agency of North Sumatra Province. SIPD is a national policy designed to integrate planning, budgeting, implementation, and financial reporting processes in order to improve transparency and accountability in regional financial management. This research employs a qualitative descriptive approach through interviews, observations, and document analysis. The analysis is based on the 5C policy implementation model, namely content, context, commitment, capacity, and clients and coalitions. The findings indicate that the implementation of SIPD has improved the efficiency and integration of financial reporting. Supporting factors include clear regulatory frameworks, leadership commitment, and the availability of basic technological infrastructure. Meanwhile, inhibiting factors consist of limited human resource competence, technical system and network constraints, and suboptimal coordination among organizational units.